The association between short‐term residential black carbon concentration on blood pressure in a general population sample. (18th February 2020) - Rabito, Felicia A.; Yang, Qiang; Zhang, Hao; Werthmann, Derek; Shankar, Arti; Chillrud, Steven
Abstract: Background: Exposure to black carbon indoors may be associated with blood pressure; however, evidence is limited to vulnerable subpopulations and highly exposed individuals. Our objective was to explore the relationship between indoor black carbon at various exposure windows on resting blood pressure in a general population sample. Methods: Black carbon was measured in the home of 76 individuals aged 10‐71 in New Orleans, Louisiana. Exposure was measured every 1 minute for up to 120 hours using an AE51 microaethalometer. Systolic blood pressure and diastolic blood pressure were measured at the conclusion of exposure monitoring. Results: In adjusted models, at all exposure windows, increasing black carbon was associated with increased systolic blood pressure. The period 0‐72 hours prior to blood pressure measurement showed the strongest effect; a 1 μg/m 3 increase in black carbon was associated with a 7.55 mm Hg ( P  = .02) increase in systolic blood pressure. The relationship was stronger in participants reporting doctor‐diagnosed hypertension (β = 6.47 vs β = 3.27). Black carbon was not associated with diastolic blood pressure. Conclusion: Increasing black carbon concentration indoors is positively associated with increasing systolic blood pressure with the most relevant exposure window being 0‐72 hours prior to blood pressure measurement. Individuals with hypertension may be a more susceptible population.